(+)‐Catechin attenuates activation of hepatic stellate cells. (10th January 2014) - Bragança de Moraes, Cristina Machado; Bitencourt, Shanna; de Mesquita, Fernanda Cristina; Mello, Denizar; de Oliveira, Leticia Paranhos; da Silva, Gabriela Viegas; Lorini, Vinicius; Caberlon, Eduardo; de Souza Basso, Bruno; Schmid, Julia; Ferreira, Gabriela Acevedo; de Oliveira, Jarbas Rodrigues
Abstract (+)‐Catechin is a type of catechin present in large amounts in açaí fruits and cocoa seeds. Besides its antioxidant and anti‐inflammatory activities, little is known about its effects in the liver, especially during hepatic fibrosis. We report here the effects of (+)‐catechin on hepatic stellate cells. (+)‐Catechin induced quiescent phenotype in GRX cells, along with an increase in lipid droplets. Proliferator‐activated receptor γ mRNA expression was upregulated, whereas type I collagen mRNA expression was downregulated. Pro‐inflammatory cytokines were not influenced by (+)‐catechin, whereas the levels of interleukin 10 were significantly increased. The data provide evidence that (+)‐catechin can reduce hepatic stellate cell activation.